Analysis of Flood Hazards and Economic Vulnerability in Productive Land in Bone District - Muhammad Munawir Syarif (Eduvest - Journal of Universal Studies, 2021)
Analysis of disaster hazards and vulnerability of the economy are thetwo essential components of disaster risk level assessments thatprovide an overview of the dangers and threats against potentiallosses when a disaster occurs in an area. Flood was a natural eventthat routinely occur each year in the Bone Regency in rainy season,when the events occurred on land or an area that is worth aproductive course would cause economic losses. The purpose of thisresearch is to find out and analyze the threat of flood hazard areasand the potential magnitude of dollars of economic losses that will becaused. Methods used in the analysis to follow general guidelines fordisaster risk assessment set by the BNPB. In the process of analysisof the danger of flooding on productive land use geographicinformation system (GIS)-based spatial data with ease in the analysisof keruangan as well as tervisualisasi served. The results of thisresearch show the danger of flood extents reach 95,247 ha. Thepotential danger of flooding to occur in Bone Regency categorizedgrades are in the area that have a spread of high danger exists inSibulue Subdistrict, Cenrana and two Boccoe. The total potential lossof the rupiah ranged from 9.5 trillion rupiah or reach 31% of the totalGDP Bone Regency with potential losses on productive landamounted to 3.3 trillion rupiah. The highest loss sector found onagricultural land amounted to 2.9 trillion rupiah.